Developing a Model for Identifying Student Talents with a Qualitative Study Approach - Sasani, Shahram; Mirzaei, Noureddine; Kamali, Naghi (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The objective of this study is to develop a comprehensive model for identifying student talents. Methods and Materials: This study used a qualitative research approach, involving semi-structured interviews with 24 students from gifted schools in Zanjan, Iran. The participants were selected through purposive sampling. Data were collected and analyzed using grounded theory and inductive coding. MAXQDA software was employed to assist in organizing and analyzing the qualitative data, leading to the extraction of open, axial, and selective codes that informed the development of the talent identification model. Findings: The study identified four primary factors influencing talent identification: individual, school, family, and social. Among these, school factors, particularly human resources (teachers, mentors), were found to be the most significant. Individual factors, such as internal and external motivation, also played a crucial role, with internal motivation being the more prominent driver of talent development. Family involvement, particularly parental support, was another key contributor, while social factors, including peer relationships, were found to be less influential but still relevant in specific contexts like sports and group activities. Conclusion: The findings suggest that talent identification is a multifaceted process influenced by a combination of individual, school, family, and social factors. School resources, including teacher support and extracurricular opportunities, are critical in fostering student talent. The study underscores the need for schools to provide equitable access to resources and teacher training to ensure that all students, particularly those from underrepresented backgrounds, have the opportunity to develop their talents.